2019
DOI: 10.1590/1980-5373-mr-2018-0757
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Fe-2.1 wt.% Si Alloy Sheets with Dominant Goss Texture Through Thickness

Abstract: Macro-and micro-texture of Fe-2.1 wt.% Si alloy sheets were investigated and analyzed by X-ray diffraction and electron backscattered diffraction techniques. A Goss ({110}<001>) component accompanied by extremely weak γ (<111>//ND, normal direction) fiber is successfully formed through the sheet thickness after primary recrystallization and considerable grain growth. Goss grains mainly nucleate at shear bands in various deformed matrices with orientations spreading from <112>//ND to <332>//ND fibers. The forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Another study reported Cube nuclei is found in both Rotated Goss {110}<110> and {111}<112> γ-fiber 18 . The high Taylor factor of these texture components results in shear bands during rolling 13,19 , which when coupled with these parent grain orientations can promote Cube nucleation. However recently Mehdi., et al, reported that Cube is nucleated preferentially from {110}<110> Rotated Goss shear bands 8 , agreeing with results reported by Xu., et al 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported Cube nuclei is found in both Rotated Goss {110}<110> and {111}<112> γ-fiber 18 . The high Taylor factor of these texture components results in shear bands during rolling 13,19 , which when coupled with these parent grain orientations can promote Cube nucleation. However recently Mehdi., et al, reported that Cube is nucleated preferentially from {110}<110> Rotated Goss shear bands 8 , agreeing with results reported by Xu., et al 9 .…”
Section: Introductionmentioning
confidence: 99%